Olympic combat sports and mental health in children and adolescents with disability: A protocol paper for systematic review - Youngjun Lee; Laura Capranica; Caterina Pesce; Flavia Guidotti; Valentin Benzing; Janet Hauck; Simone Ciaccioni (PLoS ONE, 2025)
Introduction Mental health is important for children and adolescents, particularly those with disabilities. While the mental health advantages of sports participation are well-documented, the specific type of sport may have heightened relevance for children and adolescents with disabilities. The objective of this systematic review protocol is to outline the rationale and methodology for investigating how participation in Olympic combat sports influences the mental health outcomes of this unique population, which is more susceptible to developing mental health issues than their neurotypical counterparts. Methods and analysis A comprehensive search will be conducted across academic databases, including the Cochrane Library, ERIC, PsycINFO, PubMed, Scopus, SPORTDiscus, and Web of Science. The focus will be on identifying randomized and non-randomized controlled trials (RCTs and non-RCTs, respectively), and observational studies with control groups that explore the impact of Olympic combat sports on the mental health of children and adolescents with disabilities. To assess the risk of bias, the Rob 2.0 tool will be employed for RCTs, and the ROBINS-I tool for CTs. For longitudinal and cross-sectional studies, the National Institute of Health’s Study Quality Assessment Tool for Observational Cohort and Cross-sectional Studies will be used. The review process will be conducted using Covidence, possibly utilizing JASP software for meta-analysis if the retrieved studies exhibit sufficient homogeneity. Data that cannot be included in the meta-analysis will be synthesized using the Synthesis without Meta-Analysis (SWiM) tool. Furthermore, the Consolidated Framework for Implementation Research (CFIR) will provide a framework consisting of five broad domains: intervention characteristics, outer setting, inner setting, characteristics of individuals, and the process of implementation.